High-quality genome assembly of an important biodiesel plant, Euphorbia lathyris L. (19th October 2021) - Wang, Mingcheng; Gu, Zhijia; Fu, Zhixi; Jiang, Dechun
Abstract: Caper spurge, Euphorbia lathyris L., is an important energy crop and medicinal crop. Here, we generated a high-quality, chromosome-level genome assembly of caper spurge using Oxford Nanopore sequencing, Illumina sequencing, and Hi-C technology. The final genome assembly was ∼988.9 Mb in size, 99.8% of which could be grouped into 10 pseudochromosomes, with contig and scaffold N50 values of 32.6 and 95.7 Mb, respectively. A total of 651.4 Mb repetitive sequences and 36, 342 protein-coding genes were predicted in the genome assembly. Comparative genomic analysis showed that caper spurge and castor bean clustered together. We found that no independent whole-genome duplication event had occurred in caper spurge after its split from the castor bean, and recent substantial amplification of long terminal repeat retrotransposons has contributed significantly to its genome expansion. Furthermore, based on gene homology searching, we identified a number of candidate genes involved in the biosynthesis of fatty acids and triacylglycerols. The reference genome presented here will be highly useful for the further study of the genetics, genomics, and breeding of this high-value crop, as well as for evolutionary studies of spurge family and angiosperms.